Tumor location and patient characteristics of colon and rectal adenocarcinomas in relation to survival and TNM classes - Hemminki, Kari; Santi, Irene; Weires, Marianne; Thomsen, Hauke; Sundquist, Jan; Lorenzo Bermejo, Justo (BMC cancer, 2010)
Old age at diagnosis is associated with poor survival in colorectal cancer (CRC) for unknown reasons. Recent data show that colonoscopy is efficient in preventing left-sided cancers only. We examine the association of Tumor Node Metastasis (TNM) classes with diagnostic age and patient characteristics.
Gesehen am 19.04.2023